Self-imaging of spin waves in thin, multimode ferromagnetic waveguides - Gołębiewski, Mateusz; Gruszecki, Paweł; Krawczyk, Maciej (IEEE, 2022)
Self-imaging of waves is an intriguing and spectacular effect. The phenomenon was first observed for light in 1836 by Henry Fox Talbot and to this day is the subject of research in many areas of physics, for various types of waves and in terms of different applications. This paper is a Talbot-effect study for spin waves in systems composed of a thin, ferromagnetic waveguide with a series of single-mode sources of spin waves flowing into it. The proposed systems are studied with the use of micromagnetic simulations, and the spin wave self-imaging dependencies on many parameters are examined. We formulated conditions required for the formation of self-images and suitable for experimental realization. The results of the research form the basis for the further development of self-imaging-based magnonic devices.
Keywords: magnonics; spin waves; Talbot effect; self-imaging; waveguides